2017
DOI: 10.3329/aajfss.v1i1.55757
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, molecular identification and characterization of Aeromonas hydrophila from infected air-breathing catfish Magur (Clarias batrachus) cultured in Mymensingh, Bangladesh

Abstract: The study was carried out from November, 2014 to February, 2015 with the objective of isolating Aeromonas hydrophila an important fish pathogen from infected air-breathing catfish Magur (Clarias batrachus) in Mymensingh district. Quantitative study of the isolated bacteria from infected C. batrachus was found variation of number in different organs. Total bacterial load was found to be 1.16 x 105 to 3.15 x 106 cfu/g in lesions, 2.14 x 108 to 4.17 x 109 cfu/g in liver, 1.90 x 107 to 5.12 x 108 cfu/g in spleen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In a study of A. hydrophila isolated from fish ponds in semi-intensive aquaculture in the late stage of the carp fattening cycle, 95%, 65%, and 15% of the isolates were resistant to trimethoprim, tetracycline, and chloramphenicol, respectively. Monir et al [44] isolated A. hydrophila strains from air-breathing magur catfish (Clarias batrachus) in aquaculture and found that 100% of the isolates were resistant to ampicillin, 96% were resistant to penicillin, and 92% were resistant to novobiocin. Aeromonas hydrophila strains isolated from intensive aquaculture in the Southeast Region of Brazil were moderately resistant to amoxicillin, ampicillin, lincomycin, novobiocin, oxacillin, penicillin, and tetracycline [45].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of A. hydrophila isolated from fish ponds in semi-intensive aquaculture in the late stage of the carp fattening cycle, 95%, 65%, and 15% of the isolates were resistant to trimethoprim, tetracycline, and chloramphenicol, respectively. Monir et al [44] isolated A. hydrophila strains from air-breathing magur catfish (Clarias batrachus) in aquaculture and found that 100% of the isolates were resistant to ampicillin, 96% were resistant to penicillin, and 92% were resistant to novobiocin. Aeromonas hydrophila strains isolated from intensive aquaculture in the Southeast Region of Brazil were moderately resistant to amoxicillin, ampicillin, lincomycin, novobiocin, oxacillin, penicillin, and tetracycline [45].…”
Section: Discussionmentioning
confidence: 99%
“…The freshwater air-breathing Indian catfish, C. magur (genetically distinct from C. batrachus ) ( Devassy et al, 2015 ) is a promising candidate species for freshwater aquaculture in India next to carp ( Sahoo et al, 2016 ). Magur is prone to bacterial and fungal infection in all phase of farming due to scale-less body and many Gram-negative bacterial pathogens have been reported from magur includes, A. hydrophila , A. veronii, Flavobacterium spp, Edwardsiella tarda, E. ictaluri, Pseudomonas spp ( Monir et al, 2017 ; Sharma et al, 2017 ; Sharma et al, 2018 ). There are no reports on Gram-positive bacterium causing disease in Indian magur.…”
Section: Introductionmentioning
confidence: 99%
“…Parasitic infection interferes the metabolism, and secretary functions of the alimentary canal, which affects the nervous system and causes the nutritional deficiency in the fish (Markov, 1961). Among IMC, L. rohita is found to be more susceptible to parasitic diseases than C. catla and C. mrigala (Monir et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…High stocking density in intensive systems poses the stress on fish to facilitate the opportunistic pathogens to cause diseases. In intensive aquaculture system, 15%–20% diseases are reported due to parasite infection (Monir et al., 2015). Parasitic infection interferes the metabolism, and secretary functions of the alimentary canal, which affects the nervous system and causes the nutritional deficiency in the fish (Markov, 1961).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation